PENGEMBANGAN MODUL BERORIENTASI KONSTRUKTIVISME DILENGKAPI PETA PIKIRAN PADA MATA KULIAH FISIOLOGI TUMBUHAN DI STAIN KERINCI - Angela, Lia; Razak, Abdul; Anhar, Azwir (Kolaboratif, 2013)
This research based on the previous observation and interview which was done at STAIN Kerinci, it was found that learning materials used in teaching plants physiology did not help much in constructing students’ knowledge.  This research was a developmental research which used 4-D models consisting of define, design, develop and disseminate. After the module had been designed, it was validated by four validators. To see the practicality of the module, the researcher tried out the module to VI B Biology Education students                                  of STAIN Kerinci. This activity was observed by an observer.                                                            The effectiveness test of the module is tried out to VI A Biology education students of STAIN Kerinci.  The result of the validation test showed that the constructivism-oriented module with mind map was very valid either content and construct. Based on the result of the data practicality showed that the module was practical to be used in teaching plants physiology. The module was also effective; it is showed through the improvement of student activity, motivation and achievement.